The Hypocrisy of Liberation: Power, NGOization, and Crisis in West Kalimantan Legal Aid - Moh. Fadhil; Herman, Herman (The Indonesian Journal of International Clinical Legal Education, 2025)
The structural legal aid movement was initiated by the Indonesian Legal Aid Foundation (YLBHI) as an ideological project aimed at cultivating political and legal consciousness among marginalized groups, marking a departure from conventional legal aid models grounded in legal neutrality. Despite its emancipatory narrative, the movement has become increasingly entangled in processes of NGOization, generating institutional ambivalence and dysfunction between parent and local organizations. This article examines the crisis of the structural legal aid movement in West Kalimantan by analyzing the hierarchical relationship between LBH Kalbar and YLBHI. It addresses how emancipatory ideals within the legal aid movement are undermined by NGOization, managerialism, and a fragmented civic space, and explores how power operates within the movement’s internal governance. Employing an empirical legal approach informed by socio-legal ethnography and participant observation, the study investigates organizational dynamics, work culture, and advocacy practices within LBH Kalbar. Primary data were collected through participant observation as an external supporter involved in project-based initiatives and advocacy programmes, while secondary data were drawn from internal documents accessed with institutional permission. The findings demonstrate that the decline of LBH Kalbar cannot be attributed to technical deficiencies or individual incapacity, but rather reflects a deeper ideological conflict between emancipatory praxis and a technocratic governance regime imposed by the parent organization. NGOization has redirected advocacy from community organizing toward performance-driven project work, producing depoliticization, weakened solidarity, activist burnout, and discriminatory governance practices. Power operates through disciplinary mechanisms such as standardization, performance metrics, symbolic surveillance, and organizational restructuring. The study concludes that revitalizing the legal aid movement requires not merely administrative reform, but a reconfiguration of power relations through enhanced regional autonomy and dialogical, participatory governance.